Making trade missions work : a best practice guide to international business and commercial diplomacy - Ruël, Huub (Emerald Publishing Limited, 2018)
Trade missions are a key commercial diplomacy instrument of governments around the world. Via trade missions, governments and politicians aim to promote their home country economy abroad as well as to support firms to explore and enter new markets. Despite its widespread usage, and the claims made by governments about the positive results of trade missions, actual robust evidence of trade mission effectiveness is scarce. The reason for this lack of evidence is that trade missions are mostly studied and organized in 'isolation', disconnected from the participating firms' level of international experience and international business competences. This book presents a clear view on commercial diplomacy and defines trade missions as a firm internationalization learning experience. It outlines that trade mission's preparation, programme, and follow up, are key to making trade missions work. This book presents a research informed three-staged model of a trade mission and presents in detail how a real life trade mission was organized along this model. This example should inform and inspire organizers of trade missions. The book also aims to revamp and innovate trade mission research, and will therefore be a useful source for new trade mission research for international business scholars.
Keywords: Exports.; Trade missions.; Business & Economics -- International -- General.; International business.; elektronické knihy; electronic books